Depicting Teachers’ Views on Global Competence Training - Zoe Karanikola (European Scientific Journal, ESJ, 2022)
This study refers to the scientific field of global education and competence and comes to investigate teachers' views on global competence training. This survey was conducted in June 2022, whereas the quantitative methodology was followed for the collection of the data. A random sampling technique was used, and the sample consisted of 350 teachers who worked in primary and secondary school units in the region of Western Greece during 2021-2022. Research findings show that teachers recognize the necessity and importance of training on global competence and most of them have attended one or more courses mostly during their undergraduate or postgraduate studies or during their participation in training programs. They also regard University as the most appropriate training actor, and they are in favor of optional training programs of mixed type and of monthly duration. Regarding training topics, they proposed interculturalism, diversity, current events, religion, history, immigrants, environment, geography, human rights and culture. Finally, participants’ aspects do not seem to be affected by variables such as gender and years of service. On the contrary, level of education and ICT knowledge, additional studies, and employment relationship seem to affect the answers of the participants.